The Flouting and Violating Maxims In Deadpool 2 Movie Script - Rismayanti Safitri; Ela Martisa (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2021)
This current study is aiming to find out the flouting and violating of maxims produced by characters in Deadpool 2 movie. The theory uses in this study is theory of Grice about maxims . Descriptive qualitative method is used to analyze the data. Steps in analyzing the data consist of presenting the data, describing the context of the data, interpreting the data and making the conclusion. Based on the research, It found that there are four types of flouting and violating the Grice’s maxims which derived from 22 data. 15 data that flouted the Grice’s maxims, they are 1 data flouting maxim of quantity, 6 data flouting maxim of quality, 1data flouting maxim of relation, and 7 data flouting maxim of manner. 7 data that violated the Grice’s maxims, they are 1 violating maxim of quantity, 1 violating maxim of quality, 3 violating maxim of relation, and 2 violating maxim of manner. Flouting maxim of manner becomes the most dominant types of flouting maxim, and violating maxim of relation becomes the most dominant types of violating maxim in the movie.